APPLICATION OF E-LEARNING AS A LEARNING MEDIUM FOR INFORMATION TECHNOLOGY - Rezeki, Sri Gusti; Nasution, Muhammad Irwan Padli; Sundari, Sri Suci Ayu (Transpublika Publisher, 2022)
With advances in internet network technology, information and communication services are no longer constrained by time and place constraints. Online learning emphasizes distance learning to provide the best educational process possible. Online learning is a type of information technology advancement that can be used as a teaching aid. In this work, the authors use descriptive research techniques to conduct a more in-depth analysis of the theories and trends in advances in online learning. The University of Illinois at Urbana-Champaign is a pioneer in the development of online education. In a computer-based education system, the University of Illinois has started e-learning by utilizing a computer called PLATO. The e-learning classroom learning model is a significant development in the teaching and learning process because it can reduce variations in teaching strategies and course materials and increase the consistency of learning. To prepare, with the help of technology, when everything shifts to the digital era, both in terms of methods and content, online learning systems are very important.